DUALISME TANGGUNG JAWAB HUKUM BPJS KESEHATAN DAN BPJS KETENAGAKERJAAN DALAM KASUS KECELAKAAN KERJA: TINJAUAN HUKUM PIDANA DAN PERDATA ATAS KETIDAKJELASAN PENJAMINAN PELAYANAN KESEHATAN - Gunawan Widjaja (Jurnal Kesehatan, 2026)
This study analyses the dualism of legal responsibility between BPJS Kesehatan and BPJS Ketenagakerjaan in cases of workplace accidents, focusing on the lack of clarity regarding the provision of healthcare services and its implications from the perspectives of criminal and civil law. This issue arises because, in theory, workplace accidents are covered by the Workplace Accident Insurance scheme administered by BPJS Ketenagakerjaan; however, in the practice of healthcare provision, situations frequently arise where the status of a workplace accident is still merely a presumption, meaning that initial coverage may involve BPJS Kesehatan. This study employs a normative legal methodology using a legislative approach, a conceptual approach, and a literature review of relevant legislation, legal doctrine, academic articles, and institutional sources. The findings indicate that this lack of clarity regarding coverage not only gives rise to administrative issues but also has the potential to hinder patients’ access to prompt and appropriate medical care, whilst also giving rise to legal liability for hospitals, insurers and, in certain circumstances, employers. In the civil sphere, such ambiguity may constitute grounds for a claim for tort if it results in material or non-material loss to the patient. In the criminal sphere, liability may arise where gross negligence leads to serious injury or death due to a delay in healthcare provision. This study emphasises that the dualism in legal liability stems from a lack of synchronisation between the norms and procedures of different social security providers. Therefore, regulatory harmonisation, the integration of social security systems, and certainty regarding case-handling mechanisms from the earliest stages of service provision are required to ensure that workers’ rights to health and occupational safety protection are effectively guaranteed.